2015
DOI: 10.1590/1414-431x20153646
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial cells are increased in chronic myeloid leukemia blast crisis

Abstract: We measured circulating endothelial precursor cells (EPCs), activated circulating endothelial cells (aCECs), and mature circulating endothelial cells (mCECs) using four-color multiparametric flow cytometry in the peripheral blood of 84 chronic myeloid leukemia (CML) patients and 65 healthy controls; and vascular endothelial growth factor (VEGF) by quantitative real-time PCR in 50 CML patients and 32 healthy controls. Because of an increase in mCECs, the median percentage of CECs in CML blast crisis (0.0146%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Analysis of the results obtained in the present study showed that a significant increase of ECs was observed in CML patients with blast crisis phase compared to other phases. However, in patients with chronic phase and accelerated phase the number of ECs was slightly increased compared to the control group but the differences were not statistically significant that agreed with Godoy et al [16].…”
Section: Discussionsupporting
confidence: 81%
“…Analysis of the results obtained in the present study showed that a significant increase of ECs was observed in CML patients with blast crisis phase compared to other phases. However, in patients with chronic phase and accelerated phase the number of ECs was slightly increased compared to the control group but the differences were not statistically significant that agreed with Godoy et al [16].…”
Section: Discussionsupporting
confidence: 81%
“…In many other studies, comparable mean ages were reported, such as 43.4,42, 43.3,48, 52,46, and 55. [9][10][11][12][13][14][15] In the alive group, the mean age was 43.09 ±13.09 ranging from 14-77 years with a median age of 38; in the dead group, the mean age was 37.90 ±14.20 from 3-75 with a median age of 37 years. Significantly lower mean age among the dead group, with the presence of 5 death out of 8 patients in pediatrics age group 3,12,15,16, and17 years.…”
Section: Introductionmentioning
confidence: 99%
“…Rigolin et al 47 and Gora-Tybor et al 48 found that higher levels of CECs were identified in patients with chronic lymphocytic leukemia compared to controls. Godoy et al 49 concluded that the number of CECs was increased in chronic myeloid leukemia. All of these researches also used FCM methods to measure CECs and their subpopulations; however, whether our method could be applied to hematologic malignancies such as leukemia remains to be investigated and validated.…”
Section: Discussionmentioning
confidence: 99%